STATE OF RESEARCH ON E-ASSESSMENT IN EDUCATION: A BIBLIOMETRIC ANALYSIS - Tonbuloglu, Betul (ANADOLU UNIV, 2023)
This study aimed to reveal the trend of research on e-assessment in the field of educational sciences through scientific mapping and bibliometric analyses. For this purpose, the numerical distribution of research on e-assessment, citation analysis, research themes and the change of trend topics were examined. The publications to be examined were selected from WoS database according to PRISMA model, and 911 studies were included in the analysis. VOSviewer, Biblioshiny, Smart Bibliometrics and Leximancer software were used in data analysis. Apparently, there has been a significant increase in the number of research since 2005, and publications have been mostly produced in form of articles and papers. The most cited and the most productive countries are the USA, the United Kingdom and Australia, while the most cited journals are Assessment & Evaluation in Higher Education and British Journal of Educational Technology. An analysis of the keyword map revealed that the themes of technology and motivation, blended learning and collaboration, interaction and innovative approaches, validity and reliability, higher education, quality, basic disciplines and Covid-19 were frequently emphasized in the studies on e-assessment. An analysis of trend topics by years showed that, between 2010 and 2021, the trend topic distribution changed to include topics such as Covid-19, academic integrity, engagement, cheating, case study, and higher education. All these findings reveal that e-evaluation activities have displayed a development and transformation over time with the effect of developing technology, the pandemic, the spread of e-learning, the expansion of communication opportunities and many other factors.
Keywords: E-assessment; online assessment; online evaluation; e-learning; bibliometric analysis; ONLINE FORMATIVE ASSESSMENT; STUDENTS; TEACHERS; PUBLICATIONS; METHODOLOGY; FEEDBACK; SCIENCE; WEB; Education & Educational Research